A single-cell RNA sequencing dataset of peripheral blood cells in long COVID patients on herbal therapy - Karolina Hanna Prazanowska; Tae-Hun Kim; Jung Won Kang; Young-Hee Jin; Sunoh Kwon; Su Bin Lim (Scientific Data)
Abstract Following the coronavirus disease 2019 (COVID-19) pandemic, the rise of long COVID, characterized by persistent respiratory and cognitive dysfunctions, has become a significant health concern. This leads to an increased role of complementary and alternative medicine in addressing this condition. However, our comprehension of the effectiveness and safety of herbal medicines for long COVID remains limited. Here, we present a single-cell RNA sequencing (scRNA-seq) dataset of peripheral whole blood cells derived from participants in a clinical study involving three commercially available herbal medicines, targeting fatigue and brain fog in long COVID. The dataset comprises 181,205 quality control (QC)-passed cells, along with clinical metadata, enabling a comparative analysis of immune cell populations before and after treatment. To ensure the technical validity of our dataset, we implemented rigorous quality checks throughout stages of the study, including sample preparation, sequencing, and bioinformatic data analysis levels. This transcriptomic data may serve as a resource to deepen our insights into the role of herbal medicines in management of long COVID.